The Effects of Cognition and Vision While Walking in Younger and Older Adults - Trong Pham; Meagan Suen; Young-Hee Cho; Vennila Krishnan (Sensors)
This study investigated how various cognitive tasks and visual challenges affect dual-task walking costs (DTWC) in younger and older adults. Twenty younger adults (Meanage = 22.25, SD = 3.04, 4 males) and eighteen older adults (Meanage = 71.75, SD = 5.17, 7 males) completed single-task walking and dual-task walking. The dual tasks involved walking while performing either (a) serial-subtraction by 3s or (b) a Stroop task. Both single tasks and dual tasks were performed under both normal vision and peripheral-vision-loss conditions. Results showed no significant three-way interaction but two significant two-way interactions: DTWC for step-length was greater during Stroop compared to serial-subtraction, (a) more in older adults regardless of vision (p = 0.022) and (b) more under peripheral-vision-loss regardless of age (p = 0.033). In addition, DTWC for various gait parameters was greater under (a) Stroop compared to serial-subtraction, (b) peripheral-vision-loss compared to normal vision, and (c) older adults compared to younger adults. These findings suggest that, when engaging in a cognitively demanding task, older adults place greater emphasis on maintaining gait compared to younger adults, likely to offset the negative impacts of additional cognitive load and deteriorated vision. Future research should further examine how different cognitive tasks and visual challenges interact across age groups.